Effects of CO2 and Acid Gas Injection on Enhanced Gas Recovery and Storage - Khan, Chawarwan; Amin, Robert; Madden, Gary (SpringerOpen, 2013)
Sequestration of CO2 and other associated waste gases in natural gas reservoirs is an option to mitigate greenhouse gases and enhanced gas recovery. This paper examines strategies to maximize enhanced gas recovery in a natural gas reservoir via subsurface storage of potential associated waste gases such as CO2 and H2S.Numerical simulations are performed with a compositional reservoir simulator ‘Tempest’ using experimental data initially produced by Clean Gas Technology Australia (CGTA) at Curtin University in 2009. The simulation results shows that additional gas is recovered by gas-gas displacement after injecting CO2 and acid gas (CO2–H2S) in two separate scenarios. Importantly, when pure CO2 is injected, CO2 breakthrough at the production well occurred faster than the breakthrough under mixed CO2–H2Sinjection.